Development and characterization between polyethersulfone/polysulfone (PES/PSF) micible blend with primary polymer (PES and PSF) membrane for O2/N2 separation - Sufinah, Yussof (2010)
Membrane technology becomes more interesting in industrial level for gas separation and purification. Main problem in membrane technology industries is hard to find membrane that high performance both in selectivity and permeability. Membrane that provide high permeability offered low selectivity and vice versa. Therefore, blend polymer is introduced to overcome this problem. Means that, beneficial properties of polymers are combining in one single material. In this study, four difference compositions of dope solutions have prepared which are 25% polyethersulfone (PES), 25% polysulfone (PSF), 20% polyethersulfone 5% polysulfone (PES/PSF) and 5% polyethersulfone 20% polysulfone (PES/PSF) in order to prepared the asymmetric membrane. The membrane was fabricated by using dry/wet phase inversion technique. Two type of membrane were produced from each of the sample membrane which are coated and uncoated membrane. The coating membrane was coated by coating agent, polydimethylsiloxane (PDMS). The performance of the membrane was evaluated by gas permeation unit with pure oxygen (O2) and nitrogen (N2) as a test gaseous. From the result, PES/PSF blend polymers show the best result compared the others, where the permeability value for O2 is about 19.93 GPU and N2 is 14.95 GPU whereas the selectivity of O2/N2 is 1.33. The lowest selectivity can be achieved by using primary polymer dope solution of PES and the selectivity for O2/N2 is 1.12 where the permeability of O2 is 91.84 GPU and N2 is 82.07 GPU. At 25% total polymer show not many difference to the selectivity. This is because only small amount of second polymer was added in order to blend the polymer. Then, the membrane morphology was characterized by Scanning Electron Microscopy (SEM) for identified the surface structure and cross section of the membrane. Cross section for blend polymer show the pore is smallest than primary polymer while surface structure for coated membrane is smooth as compared to uncoated membrane. From this study, by blending two type of polymer increase the performance of the membrane.